2019
DOI: 10.1038/s41386-019-0501-x
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-D-aspartate receptor antagonist d-methadone produces rapid, mTORC1-dependent antidepressant effects

Abstract: Currently available antidepressants have a delayed onset and limited efficacy, highlighting the need for new, rapid and more efficacious agents. Ketamine, an NMDA receptor antagonist, has emerged as a new rapid-acting antidepressant, effective even in treatment resistant patients. However, ketamine induces undesired psychotomimetic and dissociative side effects that limit its clinical use. The d-stereoisomer of methadone (dextromethadone; REL-1017) is a noncompetitive NMDA receptor antagonist with an apparentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 48 publications
(97 reference statements)
1
59
0
Order By: Relevance
“…Methadone is best known for treatment of opiate abuse disorder, based on the activity of l ‐methadone at opiate receptors (Gorman, Elliott, & Inturrisi, 1997). However, d ‐methadone has relatively low affinity for opiate receptor subtypes compared with l ‐methadone (Callahan, Au, Paul, Liu, & Yost, 2004), and early studies show that d ‐methadone produces antidepressant behavioral actions in the FST (Hanania, Manfredi, Inturrisi, & Vitolo, 2019) as well as several other behavioral paradigms and in the chronic unpredictable stress model (Fogaca et al, 2019). Early clinical studies have supported the possibility that d ‐methadone could be used for the treatment of depression, with fewer side effects compared to ketamine (Bernstein et al, 2019).…”
Section: Evidence That Rapid‐acting Antidepressants Increase Bdnf Relmentioning
confidence: 99%
See 1 more Smart Citation
“…Methadone is best known for treatment of opiate abuse disorder, based on the activity of l ‐methadone at opiate receptors (Gorman, Elliott, & Inturrisi, 1997). However, d ‐methadone has relatively low affinity for opiate receptor subtypes compared with l ‐methadone (Callahan, Au, Paul, Liu, & Yost, 2004), and early studies show that d ‐methadone produces antidepressant behavioral actions in the FST (Hanania, Manfredi, Inturrisi, & Vitolo, 2019) as well as several other behavioral paradigms and in the chronic unpredictable stress model (Fogaca et al, 2019). Early clinical studies have supported the possibility that d ‐methadone could be used for the treatment of depression, with fewer side effects compared to ketamine (Bernstein et al, 2019).…”
Section: Evidence That Rapid‐acting Antidepressants Increase Bdnf Relmentioning
confidence: 99%
“…Recently, d-methadone, the d-isomer of methadone that acts as an NMDA receptor antagonist, was also shown to activate the mTORC1 pathway and increase BDNF release in primary cortical cultures (Fogaca et al, 2019). Methadone is best known for treatment of opiate abuse disorder, based on the activity of l-methadone at opiate receptors (Gorman, Elliott, & Inturrisi, 1997).…”
Section: Acting Antidepressants Increase Bdnf Releasementioning
confidence: 99%
“…Recent studies have demonstrated that a single dose of scopolamine (25 µg/kg) exerts rapid antidepressant actions within days in rats (Furey et al, 2010;Drevets et al, 2013). Its antidepressant actions have been revealed to be mediated through blockade of AChM1 receptor on GABA interneurons and subsequently to increase in glutamate transmission and function of spine synapse (Voleti et al, 2013;Wohleb et al, 2016;Fogaca et al, 2019).…”
Section: Glutamate Transmissionmentioning
confidence: 99%
“…REL-1017 (esmethadone; dextromethadone), the dextro isomer of racemic d- l -methadone, is a low affinity NMDAR channel blocker with a half maximal inhibitor concentration (IC 50 ) in the micromolar range, similarly to ketamine and dextromethorphan ( Laurel Gorman et al, 1997 ; Hanania et al, 2020 ). In preclinical studies, REL-1017 improved the depressive behavior in rodent models of depression ( Fogaça et al, 2019 ; Hanania et al, 2020 ) and increased levels of synaptic proteins in the medial prefrontal cortex ( Fogaça et al, 2019 ). Mechanistic studies indicated that the antidepressant-like effects of REL-1017 observed in rodent models were mediated by mammalian target of rapamycin complex 1 (mTORC1) and BDNF induction of neural plasticity ( Fogaça et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%